2022
DOI: 10.1186/s12885-022-10133-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between the efficacy and immune-related adverse events of pembrolizumab and chemotherapy in non-small cell lung cancer patients: a retrospective study

Abstract: Background The combination of immune-checkpoint inhibitors with chemotherapy has become the standard of treatment for non-small cell lung cancer (NSCLC) patients. However, the association between therapeutic efficacy and the development of immune-related adverse events (irAEs) remains unclear in patients treated with combination therapy. We aimed to investigate the frequency of irAEs, and the association between therapeutic efficacy and the development of irAEs in patients with NSCLC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
1
5
1
Order By: Relevance
“…The incidence of reported irAEs in NSCLC varies widely, ranging from 24.0% to 70.5%. This reflects heterogeneity including in study setting (observational vs randomized clinical trial), patient characteristics (cancer stage, PD-L1 status, geographical location, race and ethnicity), treatment parameters (ICI agent used either alone or combined with chemotherapy, treatment line), and irAE grading . In our cohort, the incidence of clinically meaningful irAEs was 37.0%.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The incidence of reported irAEs in NSCLC varies widely, ranging from 24.0% to 70.5%. This reflects heterogeneity including in study setting (observational vs randomized clinical trial), patient characteristics (cancer stage, PD-L1 status, geographical location, race and ethnicity), treatment parameters (ICI agent used either alone or combined with chemotherapy, treatment line), and irAE grading . In our cohort, the incidence of clinically meaningful irAEs was 37.0%.…”
Section: Discussionmentioning
confidence: 96%
“…31,55 The median time to developing an irAE in our study population was 3.4 months, longer than that typically cited in the NSCLC literature. 24,[36][37][38] However, we only recorded clinically meaningful irAEs per our definition, and studies have shown low-grade events develop earlier than high-grade events. 34,39 The incidence of reported irAEs in NSCLC varies widely, ranging from 24.0% to 70.5%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been controversial whether ICI combined with chemotherapy has an effect on irAEs. 48 , 49 However, the sample size was smaller under different ICI treatment strategies when analysed by univariate logistic regression. Conclusions related to factors influencing ICI-related pAEs need to be further validated by larger studies or clinical trials.…”
Section: Discussionmentioning
confidence: 98%
“…Two studies reporting PD-1 inhibitors in combination with chemotherapy found that overall irAE was associated with a PFS benefit. 24,25 Nonetheless, due to their small sample sizes and short follow-up periods, these studies failed to analyze OS or investigate organ-specific irAE. In a recent meta-analysis that included 62 randomized clinical studies, the investigators concluded that irAE should not be seen as a proxy for OS of anti-PD-1 treatment, 26 which is in agreement with our findings.…”
Section: Discussionmentioning
confidence: 99%